2016
DOI: 10.1007/s11606-016-3700-8
|View full text |Cite
|
Sign up to set email alerts
|

At-Home Versus In-Clinic INR Monitoring: A Cost–Utility Analysis from The Home INR Study (THINRS)

Abstract: BACKGROUND: Effective management of patients using warfarin is resource-intensive, requiring frequent inclinic testing of the international normalized ratio (INR). Patient self-testing (PST) using portable at-home INR monitoring devices has emerged as a convenient alternative. As revealed by The Home INR Study (THINRS), event rates for PST were not significantly different from those for in-clinic high-quality anticoagulation management (HQACM), and a cumulative gain in quality of life was observed for patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
0
13
0
3
Order By: Relevance
“…A recent meta-analysis of 22 studies found that self-testing improved outcomes, but could not judge its costeffectiveness. 2 The current study by Phibbs et al 3 addresses this gap in evidence.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…A recent meta-analysis of 22 studies found that self-testing improved outcomes, but could not judge its costeffectiveness. 2 The current study by Phibbs et al 3 addresses this gap in evidence.…”
mentioning
confidence: 82%
“…4 The THINRS investigators found that self-monitoring had equivalent outcomes to traditional monthly monitoring and led to higher self-reported health-related quality of life as measured by the Health Utilities Index. Phibbs and colleagues 3 have followed these findings up with a cost-utility analysis to address the question: BIs this parity in outcomes but improvement in health-related quality of life worth paying for?^.…”
mentioning
confidence: 99%
“…A dose média semanal do ACO foi semelhante entre os grupos (µ=42,5 S=15,0 para o GI e µ=39,7 S=16 para o GC), corroborando com os resultados de outros estudos (VERRET et al, 2012;SILVA DE ASSIS et al, 2012;PELEGRINO, 2013;MATCHAR et al, 2015;PHIBBS et al, 2016).…”
Section: -Desfechosunclassified
“…Quanto às comorbidades consideradas como fatores de risco para a instabilidade do INR na faixa terapêutica adequada, a maioria dos participantes tinha diagnóstico de hipertensão arterial (61,5% para ambos os grupos). Os resultados se assemelharam aos de outros estudos, que apresentaram frequência entre 51% e 85,3%, para a mesma comorbidade (CORBI et al, 2011;BOLELA , 2013;DIER, 2010;STOUDENMIRE;DE REMER;ELEWA, 2014, PHIBBS et al, 2016. A dislipidemia foi a segunda comorbidade mais frequente entre os participantes (26,9% para o GI e 38,5% para o GC), seguida da Diabetes…”
Section: -Desfechosunclassified
See 1 more Smart Citation